Authenticated Encryption Schemes: A Systematic Review - Jimale M.A.; Z'Aba M.R.; Kiah M.L.B.M.; Idris M.Y.I.; Jamil N.; Mohamad M.S.; Rohmad M.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cryptography; Efficiency; Authenticated encryption; CAESAR competition; Classification algorithm; Confidentiality; Integrity; Message authentication codes; NIST; NIST-LW competition; Security; Systematic; Authentication